Combining Ability of Early-Maturing Yellow Maize Inbreds under Combined Drought and Heat Stress and Well-Watered Environments - Laouali M. Nasser; Baffour Badu-Apraku; Vernon E. Gracen; Hortense N. A. Mafouasson (Agronomy, 2020)
Grain-yield potential of maize (Zea mays L.) is limited by the harsh climatic conditions during dry seasons in the savanna of sub-Saharan Africa (SSA). One hundred and five hybrids derived from diallel crosses involving 15 early-maturing yellow maize inbreds were screened under combined drought and heat stress (CDHS) and well-watered (WW) conditions at four locations representative of the dry savannas of Niger, 2012–2014. The objective of the study was to examine the general combining ability (GCA) effects of the inbred lines and specific combining ability (SCA) of the crosses under CDHS and WW environments, assess yield and stability of the derived hybrids under contrasting environments and investigate inter-relationships among traits of the hybrids under contrasting environments. GCA and SCA effects for grain yield and other measured traits were significant, with preponderance of GCA effects over SCA effects under both the CDHS and WW environments. Inbred ENT 13 possessed positive and significant GCA effects for grain yield under both CDHS and WW environments indicating that the inbred could be used for developing outstanding hybrids with good levels of tolerance to CDHS. This also implied that the inbred line could serve as invaluable genetic resource for introgression of favorable alleles into tropical early-maturing maize populations for accelerated genetic gains from selection for improved grain yield. Hybrids ENT 13 × TZEI 167 and TZEI 157 × ENT 13 were the most stable and among the highest yielding hybrids across research environments. These outstanding hybrids could be tested extensively for commercialization in SSA to improve food security. Plant and ear aspects and days to 50% silking could be combined with grain yield in a selection index for improvement of yield under CDHS without yield penalties under WW environments.